Peran Auditor Internal dalam Consulting Perusahaan - Ramadani Meta Pertiwi; Wina Aditya Putri Wibowo; Intan Widiyaningsih; Rodiatam Mardiah; Yuni Sukandani (Universitas Katolik Widya Karya Malang, 2024)
. Internal auditors play a strategic role in ensuring the transparency, integrity, and operational efficiency of an organization. This article explains how internal auditors function as consultants providing advice to improve a company's risk management, control and governance processes, IA also identifies and manages risks that may affect organizational objectives. By using appropriate audit methodologies and utilizing modern audit technology, internal auditors can add significant value by providing recommendations for process improvements and internal controls. Amid challenges such as limited resources and pressure to deliver accurate and relevant results in a timely manner, internal auditors must be able to maintain their independence and ensure effective collaboration with senior management and the audit committee. Keywords for this article include: auditor, consulting and company. Considering the challenges and opportunities faced, this article summarizes the crucial role of internal auditors in supporting the long-term success of companies through careful oversight and strategic recommendations for risk management and improving company performance.